Emergent quantum phenomena under peculiar disorder and non-trivial topology - Ribeiro, Cauê Kaufmann (2025)
Emergent quantum phenomena in condensed matter physics provide a fertile ground for uncovering new states of matter and understanding the interplay between electronic correlations and topology. This thesis explores these phenomena in systems realized as quantum materials: the cage compound FeGa3 and the topological Dirac material ZrTe5. For FeGa3, we investigate how a peculiar disorder, known as antisite Fe defects, tunes the electronic and magnetic ground states, unveiling unconventional semiconducting phases, quantum criticality, and strongly correlated metallic behavior. Comprehensive analyses of electrical transport, magnetization,Mössbauer spectroscopy, and heat capacity under varying pressures and temperatures reveal a complex phase diagramwhere disorder-induced electronic correlations play a central role. Additionally, we describe our methodology for the synthesis of this material and subsequent crystallographic structural analyses using state-of-the-art data analysis techniques. For ZrTe5, we focus on the rarely explored physics above its quantum limit, including unconventional magnetoresistance oscillations and relativistic effects in Landau level dispersion. Utilizing high-field electrical transport and magnetometry, we reveal that these oscillations arise from relativistic corrections to Dirac electrons behavior, offering new insights into topological materials under extreme conditions. This work advances our understanding of quantum materials by establishing a framework for exploring disorder-induced correlations and relativistic effects.